Strategi Manajemen Perubahan dalam Membangun Jiwa Kepemimpinan Mahasiswa Universitas Islam Negeri Sumatera Utara - Epa Purnama Sari Harahap; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
Change management strategy in building leadership spirit is something that a student must have in taking action, so that in taking an action or a decision a student must have a leadership spirit in himself and make a change management for the better. Therefore, a student really needs change management within himself and within the company, organizations also need change management within the company, the organization so that the company is better and more advanced than before. And students of the State Islamic University of North Sumatra have a passion for organizational change for the better in the future.